2000
DOI: 10.1073/pnas.97.3.1224
|View full text |Cite
|
Sign up to set email alerts
|

Correction of ornithine accumulation prevents retinal degeneration in a mouse model of gyrate atrophy of the choroid and retina

Abstract: Deficiency of ornithine-␦-aminotransferase (OAT) in humans results in gyrate atrophy of the choroid and retina (GA), an autosomal recessive disorder characterized by ornithine accumulation and a progressive chorioretinal degeneration of unknown pathogenesis. To determine whether chronic, systemic reduction of ornithine can prevent this form of retinal degeneration, we used an argininerestricted diet to maintain long term reduction of ornithine in a mouse model of OAT-deficiency (Oat ؊͞؊ ) produced by gene targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 29 publications
2
45
0
1
Order By: Relevance
“…[11][12][13] Dietary restriction of arginine has been shown to prevent (but not reverse) retinal degeneration in OAT-deficient mice. 14 In humans, the impacts of this treatment have been more varied, with results ranging from visual improvement, [15][16][17] marked delay of, [18][19][20][21] modest delay of, 22,23 to no discernable bearing on 24 the progression of ocular symptoms. Better outcomes in patients with GACR may correlate with earlier implementation of arginine restriction, more rigorous compliance with the dietary regimen, or both.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Dietary restriction of arginine has been shown to prevent (but not reverse) retinal degeneration in OAT-deficient mice. 14 In humans, the impacts of this treatment have been more varied, with results ranging from visual improvement, [15][16][17] marked delay of, [18][19][20][21] modest delay of, 22,23 to no discernable bearing on 24 the progression of ocular symptoms. Better outcomes in patients with GACR may correlate with earlier implementation of arginine restriction, more rigorous compliance with the dietary regimen, or both.…”
Section: Introductionmentioning
confidence: 99%
“…In some GA patients, enlargement of the atrophic area was found without any increase in the plasma level of L-Orn. 13,[18][19][20] In addition, L-Orn-loaded GA relatives and patients of HHH syndrome did not develop retinal degeneration, although the plasma concentration of them were 600-1100 µM. 31) Thus, it is unlikely that only L-Orn accumulation in the plasma would be a direct cause of RPE degeneration in GA.…”
Section: Discussionmentioning
confidence: 99%
“…17,18) In other patients, enlargement of the atrophic area was found despite biochemical control of the plasma level of L-Orn. 13,19) Furthermore, cases of GA-like traits have been reported without any increase in the plasma level of L-Orn. 20,21) Thus, it has been unclear whether L-Orn accumulation in the plasma is a direct cause of RPE degeneration in GA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been suggested that increase of ornithine levels might be involved in vigabatrin-associated visual field defects (Roubertie et al 1998;Sorri et al 2010) as a result of ornithine-d-aminotransferase (OAT) impairment. In some patients with gyrate atrophy, vitamin B6 substitution has been successfully employed to prevent the loss of vision (Wang et al 2000;Ohkubo et al 2005;Sorri et al 2010). In line with this observation, and in order to prevent a worsening of the visual defect, we implemented a pyridoxine supplementation (300 mg/day) in conjunction with the same dosage of vigabatrin.…”
Section: Discussionmentioning
confidence: 99%